Pengaruh Store Atmosphere Terhadap Minat Beli Wisatawan Di Pasar Seni Sukawati Kabupaten Gianyar - Riantra, Andreas Agung; Sukana, Made (JURNAL DESTINASI PARIWISATA; Vol 7 No 2 (2019): VOL 7, NO 2 (2019): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2019)
The research is conducted to find out how the condition of the store atmosphere in Sukawati Art Market and to find out the influence of store atmosphere towards tourists’ purchase intention in Sukawati Art Market. The methods used in this research is descriptive quantitative.The samples are determined by the slovin formula, as many as 100 out of 75,000 population. Data are collected through observation, questionnaires, literature studies, and visual materials. Data are analyzed by multiple linear regression, hypothesis testing using t test and F test. The result of the research shows that partially store general interior significantly influence tourists’ buying interest in Sukawati Art Market as the t test score is bigger than t table score 1,988 which is the t score is 2,135. Also store general exterior significantly influence tourist’s buying interest as the t test score is 3,138. Simultaneously, both store and general interior are significantly influence tourists’ buying interest in Sukawati Art Market as the f test score is 15,700. Keywords : Store Atmosphere, Tourist Buying Interest, Sukawati Art Market, Traditional Art Market